2021
DOI: 10.9734/jalsi/2021/v24i1230277
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-temporal Assessment of Phytoplankton and Physicochemical Parameters of Dangana Lake, Lapai, Niger State Nigeria

Abstract: Dangana Lake was constructed primarily to provide water for drinking, domestic activities and control flood. Phytoplankton assemblage and physicochemical parameters of Dangana Lake, Lapai, Niger State Nigeria were investigated monthly between March and October 2019 using standard methods and procedures. Water samples were collected from 3 different stations in the Lake. The result of the lake shows water temperature (23.2-29.5ºC), Biochemical oxygen Demand (2.30-3.91mg/l), Dissolved oxygen (3.40-4.70mg/l), wat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 12 publications
2
3
0
Order By: Relevance
“…The contours of the drainage area and the amount of rainfall typically have an impact on the water level in the aquatic ecosystem. (Adamu et al, 2021). Most of the physicochemical values recorded during this study reflect a typical tropical climate environment, as previously reported in other studies in Nigeria (Mohammed et al, 2020;Mohammed et al, 2021;Edegbene et al, 2022;Adamu et al, 2022;Maishanu et al, 2022;Ebesi et al, 2022;Adama et al, 2023).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The contours of the drainage area and the amount of rainfall typically have an impact on the water level in the aquatic ecosystem. (Adamu et al, 2021). Most of the physicochemical values recorded during this study reflect a typical tropical climate environment, as previously reported in other studies in Nigeria (Mohammed et al, 2020;Mohammed et al, 2021;Edegbene et al, 2022;Adamu et al, 2022;Maishanu et al, 2022;Ebesi et al, 2022;Adama et al, 2023).…”
Section: Discussionsupporting
confidence: 86%
“…The most precious natural resource that is accessible to humans is water, which is essential for life. Water bodies are used for a variety of purposes, including as a source of water for drinking, washing clothes, irrigation, and hydropower generation (Adamu et al, 2021). In order for human and animal socioeconomic development to be significant in any community, there must be a sufficient and safe water supply (Mohammed et al, 2020;Kılıç, et al, 2020;Mohammed et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…The research study was carried out to assess the effect of flood on water quality and plankton assemblage of two water bodies in Bosso Area, Minna, Niger State. The mean value of the water temperature recorded for both water bodies in this study was typical of tropical inland fresh water and rivers (Adamu et al, 2021;Adamu et al, 2022). The temperature ranged observed from both water bodies fells within the permissible limits of WHO guideline for drinking water and aquatic life sustainability.…”
Section: Discussionsupporting
confidence: 59%
“…Since diatoms react directly and sensitively to a wide range of physical, chemical, and biological changes that take place in the aquatic environment, they are important environmental indicators (Ekhator et al, 2015, Ebesi et al, 2022. In favourable circumstances, diatom blooms have the potential to harm other biological systems (Adamu et al, 2021;Ebesi et al, 2021). A river's phytoplankton diversity, quantity, and distribution are directly correlated with the water quality and, by extension, the composition of the entire community (Adamu et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Freshwater pollution by human activities is becoming a matter of urgent concern as it threatens environmental productivity and sustainability (Mohammed et al, 2020;Mohammed et al, 2021). Numerous anthropogenic activities such as an increase in urbanization, industrialization and increased agricultural activities have significantly increased pressure on freshwater resources thereby altering the physical, chemical and biological uniqueness of these natural resources (Adamu et al, 2021;Ebesi et al, 2022;Adamu et al, 2022). The physical and chemical characteristics of freshwater coupled with their biological characteristics have been used to ascertain the ecological health of freshwater bodies (Adamu et al, 2021;Ebesi et al, 2022;Adamu et al, 2022;Mohammed et al, 2023).…”
Section: Introductionmentioning
confidence: 99%